Penguatan Pendidikan Karakter Siswa SD Melalui Kearifan Lokal - Masruroh Masruroh; Moch Rio Pambudi; Ayub Pratama Aris; Ninasafitri Ninasafitri; Aang Panji Permana (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2022)
Character education is an effort to prevent the growth of bad characters for the younger generation, especially through the introduction of local wisdom cultural values. Character values that must be instilled in students in the current era of very rapid technological development is by providing character education which includes knowledge, awareness and action to be implemented in everyday life. The purpose of this community service is to provide strengthening character education through local wisdom of SDN 03 Kabila Bone students in Molotabu Village, Gorontalo. The target of this activity is elementary school students. The method used in this community service activity is student participation. Involve students directly with assistance during activities. The results of the evaluation showed that all educators followed the character education strengthening material with the results that 89% of participants were in the good category and 11% in the sufficient category. Thus strengthening character education through local wisdom can be said to be good by providing socialization and concrete actions that will be remembered by students in preserving and caring for the environment. This activity is expected to have a positive impact as an educational effort for students at SDN 03 Kabila Bone, Molotabu village, Gorontalo.